Microbial bioremediation of petroleum hydrocarbons in soil microcosms - Pellizzer, Elisa Pais [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
Contamination by petroleum hydrocarbons poses significant environmental and health risks due to their toxicity and persistence in ecosystems. As global petroleum production continues to rise, the risks associated with such contamination remain a pressing concern. This challenge highlights the need for effective soil remediation techniques, particularly microbial bioremediation. By leveraging the enzymatic potential of microorganisms, bioremediation offers a promising approach to mitigating the environmental damage caused by petroleum hydrocarbons. Although numerous studies have investigated microbial bioaugmentation and biostimulation for the remediation of contaminated soils, few have examined hydrocarbon degradation and detoxification over time. Furthermore, most bioremediation studies have been conducted over short experimental periods, with relatively few extending beyond 120 days. Given the highly dynamic nature of microbial communities in petroleumcontaminated environments, there is still a limited understanding of how native and introduced microorganisms interact over extended periods and how these interactions impact bioremediation success. The present study aims to address these gaps by investigating the long-term hydrocarbon degradation and microbial community dynamics in petroleum-contaminated soils, providing new insights into the stability, efficiency, and sustainability of bioremediation approaches. This thesis aims to (i) develop a microbial consortium for the bioaugmentation of petroleum-contaminated soil microcosms, (ii) apply bioremediation treatments in petroleum-contaminated soil under controlled microcosm conditions, and (iii) investigate the ecological dynamics of bacterial and fungal communities during bioremediation. The study is structured in five chapters: general introduction (Chapter 1), three experimental chapters (Chapters 2, 3, and 4), and a concluding chapter (Chapter 5). Chapter 2 focuses on developing a microbial consortium for bioaugmentation in petroleum-contaminated soil. This consortium is based on the filamentous fungus Aspergillus sclerotiorum CBMAI 849. It was developed through antagonism tests involving microorganisms from marine environments. These tests revealed no antagonism between A. sclerotiorum and Trichoderma harzianum CBMAI 1229, leading to their selection as a fungal consortium. This chapter highlights the importance of considering microbial interactions when designing effective bioaugmentation strategies for petroleum-contaminated environments. Chapter 3 evaluates the effectiveness of different bioremediation strategies, including natural attenuation, biostimulation, bioaugmentation, and a combination of biostimulation and bioaugmentation, in microcosm experiments. The marine fungal consortium developed in Chapter 2 was applied in the bioaugmentation treatment. The study monitored the degradation of alkanes and polycyclic aromatic hydrocarbons (PAHs), enzymatic activities, and phytotoxicity over 60, 120, and 180 days. The results showed that bioaugmentation enhanced alkane degradation, while biostimulation promoted the degradation of PAHs and reduced soil toxicity. The combined biostimulation/bioaugmentation not only facilitated alkane and PAH degradation but also promoted the breakdown of high molecular weight alkanes. Microbial community analyses revealed a succession of hydrocarbon-degrading bacteria and fungi, emphasizing the importance of temporal dynamics in bioremediation. Chapter 4 explores the ecological dynamics of microbial communities involved in bioremediation, focusing on the structure and drivers of bacterial and fungal populations under hydrocarbon contamination. By examining the effects of biostimulation, bioaugmentation, and their combined application, this chapter aims to elucidate how these interventions influence microbial interactions over time. The study found that bacterial communities tended to converge across treatments, particularly in nutrient-rich conditions, while fungal communities exhibited greater divergence, indicating different adaptive strategies. Rare microbial taxa became dominant during the bioremediation process, suggesting their crucial role in hydrocarbon degradation. Furthermore, bioaugmentation appeared to drive deterministic selection in bacterial communities, while biostimulation primarily influenced the growth of bacteria dependent on available nutrients. This chapter concludes that both biostimulation and bioaugmentation significantly impact microbial dynamics, enhancing hydrocarbon degradation through distinct ecological processes. Finally, Chapter 5 synthesizes the findings to address the primary research questions, discussing their implications, the limitations encountered, and potential directions for future research in microbial-based bioremediation. This thesis underscores the critical role of microorganisms and their ecological dynamics in the bioremediation of petroleum-contaminated soil.

A contaminação por hidrocarbonetos de petróleo implica riscos ambientais e à saúde significativos devido à sua toxicidade e persistência nos ecossistemas. À medida que a produção global de petróleo continua a aumentar, os riscos associados a essa contaminação permanecem uma preocupação urgente. Este desafio destaca a necessidade de técnicas eficazes de remediação do solo, particularmente a biorremediação microbiana. Ao alavancar o potencial enzimático dos microrganismos, a biorremediação oferece uma abordagem promissora para mitigar os danos ambientais causados pelos hidrocarbonetos de petróleo. Embora numerosos estudos tenham investigado a bioaumentação e a bioestimulação microbiana para a remediação de solos contaminados, poucos avaliaram a degradação e a destoxificação de hidrocarbonetos ao longo do tempo. Além disso, a maioria dos estudos de biorremediação foi conduzida em curtos períodos experimentais, com relativamente poucos se estendendo além de 120 dias. Dada a natureza altamente dinâmica das comunidades microbianas em ambientes contaminados por petróleo, ainda há uma compreensão limitada de como os microrganismos nativos e introduzidos interagem por longos períodos e como essas interações impactam no sucesso da biorremediação. O presente estudo visa abordar essas lacunas investigando a degradação de hidrocarbonetos a longo prazo e a dinâmica da comunidade microbiana em solos contaminados por petróleo, fornecendo novos insights sobre a estabilidade, eficiência e sustentabilidade das abordagens de biorremediação. Esta tese tem por objetivos (i) desenvolver um consórcio microbiano para a bioaumentação de microcosmos de solo contaminado por petróleo, (ii) aplicar tratamentos de biorremediação em solo contaminado por petróleo sob condições controladas de microcosmos e (iii) investigar a dinâmica ecológica das comunidades bacterianas e fúngicas durante a biorremediação. O estudo está estruturado em cinco capítulos: introdução geral (Capítulo 1), três capítulos experimentais (Capítulos 2, 3 e 4) e um capítulo conclusivo (Capítulo 5). O Capítulo 2 concentra-se no desenvolvimento de um consórcio microbiano para bioaumentação em solo contaminado por petróleo. Este consórcio é baseado no fungo filamentoso Aspergillus sclerotiorum CBMAI 849 e foi desenvolvido por meio de testes de antagonismo envolvendo microrganismos de ambientes marinhos. Esses testes não revelaram antagonismo entre A. sclerotiorum e Trichoderma harzianum CBMAI 1229, levando à sua seleção como um consórcio fúngico. Este capítulo destaca a importância de considerar as interações microbianas ao projetar estratégias eficazes de bioaumentação para ambientes contaminados por petróleo. O Capítulo 3 avalia a eficácia de diferentes estratégias de biorremediação, incluindo atenuação natural, bioestimulação, bioaumentação e uma combinação de bioestimulação e bioaumentação, em experimentos em microcosmos. O consórcio fúngico marinho desenvolvido no Capítulo 2 foi aplicado no tratamento de bioaumentação. O estudo monitorou a degradação de alcanos e hidrocarbonetos policíclicos aromáticos (HPAs), atividade enzimática e fitotoxicidade ao longo de 60, 120 e 180 dias. Os resultados mostraram que a bioaumentação aumentou a degradação de alcanos, enquanto a bioestimulação promoveu a degradação de HPAs e reduziu a toxicidade do solo. A combinação bioestimulação/bioaumentação não apenas facilitou a degradação de alcanos e HPAs, mas também promoveu a quebra de alcanos de alto peso molecular. As análises da comunidade microbiana revelaram uma sucessão de bactérias e fungos degradadores de hidrocarbonetos, enfatizando a importância da dinâmica temporal na biorremediação. O Capítulo 4 explora a dinâmica ecológica das comunidades microbianas envolvidas na biorremediação, com foco na estrutura e nos fatores determinantes das populações bacterianas e fúngicas sob contaminação por hidrocarbonetos. Ao examinar os efeitos da bioestimulação, bioaumentação e suas aplicações combinadas, este capítulo visa elucidar como essas intervenções influenciam as interações microbianas ao longo do tempo. O estudo constatou que as comunidades bacterianas tenderam a convergir entre os tratamentos, particularmente em condições ricas em nutrientes, enquanto as comunidades fúngicas exibiram maior divergência, indicando diferentes estratégias adaptativas. Táxons microbianos raros tornaram-se dominantes durante o processo de biorremediação, sugerindo seu papel crucial na degradação de hidrocarbonetos. Além disso, a bioaumentação indicou impulsionar a seleção determinística em comunidades bacterianas, enquanto a bioestimulação influenciou principalmente o crescimento de bactérias dependentes dos nutrientes disponíveis. Este capítulo conclui que tanto a bioestimulação quanto a bioaumentação impactam significativamente a dinâmica microbiana, aumentando a degradação de hidrocarbonetos por meio de processos ecológicos distintos. Por fim, o Capítulo 5 sintetiza os resultados para abordar as principais questões da pesquisa, discutindo suas implicações, as limitações encontradas e as possíveis direções para futuras pesquisas em biorremediação baseadas em microrganismos. Esta tese destaca o papel crítico dos microrganismos e sua dinâmica ecológica na biorremediação de solos contaminados com petróleo.

Verontreiniging door aardolieproducten vormt een aanzienlijk risico voor het milieu en de volksgezondheid vanwege hun toxiciteit en persistentie in ecosystemen. Nu de wereldwijde aardolieproductie blijft stijgen, blijven de risico’s die met deze verontreiniging gepaard gaan een urgente zorg. Deze uitdaging onderstreept de noodzaak van effectieve bodemsaneringsmethoden, net zo als microbiële bioremediatie. Door gebruik te maken van het enzymatische potentieel van microorganismen biedt bioremediatie een veelbelovende aanpak om milieuschade veroorzaakt door aardolieproducten te beperken. Hoewel talrijke studies microbiële bioaugmentatie en biostimulatie voor de sanering van verontreinigde bodems hebben onderzocht, hebben slechts weinigen zich gericht op de afbraak en detoxificatie van koolwaterstoffen in de tijd. Bovendien zijn de meeste bioremediatiestudies uitgevoerd over korte experimentele perioden, waarbij relatief weinig studies verder gingen dan 120 dagen. Gezien de sterk dynamische aard van microbiële gemeenschappen in met aardolie verontreinigde omgevingen, is er nog steeds een beperkt inzicht in hoe inheemse en geïntroduceerde micro-organismen op lange termijn met elkaar interageren en hoe deze interacties de effectiviteit van bioremediatie beïnvloeden. Deze studie beoogt deze kennishiaten te overbruggen door de langetermijnafbraak van koolwaterstoffen en de dynamiek van microbiële gemeenschappen in met aardolie verontreinigde bodems te onderzoeken. Dit zal nieuwe inzichten opleveren in de stabiliteit, efficiëntie en duurzaamheid van bioremediatiebenaderingen. Deze thesis heeft als doel: (i) het ontwikkelen van een microbiële consortium voor bioaugmentatie van met aardolie verontreinigde bodemmicrokosmos, (ii) het toepassen van bioremediatiebehandelingen onder gecontroleerde microkosmosomstandigheden, en (iii) het onderzoeken van de ecologische dynamiek van bacteriële en schimmelgemeenschappen tijdens de bioremediatie. De studie is opgebouwd uit vijf hoofdstukken: een algemene inleiding (Hoofdstuk 1), drie experimentele hoofdstukken (Hoofdstukken 2, 3 en 4) en een concluderend hoofdstuk (Hoofdstuk 5). Hoofdstuk 2 richt zich op de ontwikkeling van een microbiële consortium voor bioaugmentatie in met aardolie verontreinigde bodem. Dit consortium is gebaseerd op de draadvormige schimmel Aspergillus sclerotiorum CBMAI 849 en werd ontwikkeld via antagonismetests met micro-organismen uit mariene omgevingen. Deze tests toonden geen antagonisme aan tussen A. sclerotiorum en Trichoderma harzianum CBMAI 1229, wat leidde tot hun selectie als schimmelconsortium. Dit hoofdstuk benadrukt het belang van microbiële interacties bij het ontwerpen van effectieve bioaugmentatiestrategieën voor met aardolie verontreinigde omgevingen. Hoofdstuk 3 evalueert de effectiviteit van verschillende bioremediatiestrategieën, waaronder natuurlijke attenuatie, biostimulatie, bioaugmentatie en een combinatie van biostimulatie en bioaugmentatie, in microkosmosexperimenten. Het in hoofdstuk 2 ontwikkelde mariene schimmelconsortium werd toegepast in de bioaugmentatiebehandelingen. De studie volgde de afbraak van alkanen en polycyclische aromatische koolwaterstoffen (PAK’s), enzymatische activiteiten en fytotoxiciteit gedurende 60, 120 en 180 dagen. De resultaten toonden aan dat bioaugmentatie de afbraak van alkanen verbeterde, terwijl biostimulatie de afbraak van PAK’s bevorderde en de bodemtoxiciteit verminderde. De gecombineerde toepassing van biostimulatie en bioaugmentatie versnelde niet alleen de afbraak van alkanen en PAK’s, maar bevorderde ook de afbraak van alkanen met een hoog molecuulgewicht. Analyses van microbiële gemeenschappen toonden een opeenvolging aan van bacteriën en schimmels die koolwaterstoffen afbreken, wat het belang van temporele dynamiek in bioremediatie benadrukt. Hoofdstuk 4 onderzoekt de ecologische dynamiek van microbiële gemeenschappen die betrokken zijn bij bioremediatie, met de nadruk op de structuur en drijvende krachten van bacteriële en schimmelpopulaties onder koolwaterstofverontreiniging. Door de effecten van biostimulatie, bioaugmentatie en hun gecombineerde toepassing te analyseren, wil dit hoofdstuk verduidelijken hoe deze interventies microbiële interacties in de tijd beïnvloeden. De studie toonde aan dat bacteriële gemeenschappen de neiging hadden om te convergeren tussen de behandelingen, vooral onder nutriëntenrijke omstandigheden, terwijl schimmelgemeenschappen grotere divergentie vertoonden, wat wijst op verschillende aanpassingsstrategieën. Zeldzame microbiële taxa werden dominant tijdens het bioremediatieproces, wat suggereert dat ze een cruciale rol spelen in de afbraak van koolwaterstoffen. Daarnaast leek bioaugmentatie een deterministische selectie in bacteriële gemeenschappen te stimuleren, terwijl biostimulatie vooral de groei beïnvloedde van bacteriën die afhankelijk zijn van beschikbare nutriënten. Dit hoofdstuk concludeert dat zowel biostimulatie als bioaugmentatie aanzienlijke invloed hebben op microbiële dynamiek en de afbraak van koolwaterstoffen bevorderen via verschillende ecologische processen. Tot slot synthetiseert hoofdstuk 5 de bevindingen om de centrale onderzoeksvragen te beantwoorden, bespreekt hun implicaties, de ondervonden beperkingen en mogelijke richtingen voor toekomstig onderzoek naar microbiële bioremediatie. Deze thesis benadrukt de cruciale rol van micro-organismen en hun ecologische dynamiek in de sanering van met aardolie verontreinigde bodems.
Biorremediação microbiana de hidrocarbonetos de petróleo em microcosmos de solo
Keywords: Marine fungi; Phytotoxicity; Environmental biotechnology; Microbial ecology; Fungos marinhos; Fitotoxicidade; Biotecnologia ambiental; Ecologia microbiana